Dose calculation and dosimetry tests for clinical implementation of 1D tissue-deficit compensation by a single dynamic absorber - Corletto, Daniela; Fiorino, Claudio; Cattaneo, Giovanni Mauro; Mangili, Paola; Calandrino, Riccardo (Radiotherapy and oncology, 1998)
Background and purpose: In this study the possibilities for implementing 1D tissue-deficit compensation techniques by a dynamic single absorber were investigated. This research firstly involved a preliminary examination on the accuracy of a pencil beam-based algorithm, implemented for irregularly shaped photon beams in our 3D treatment planning system (TPS) (Cadplan 2.7, Varian-Dosetek Oy), in calculating dose distributions delivered in 1D non-uniform fields. Once the reliability of the pencil beam (PB) algorithm for dose calculations in non-uniform beams was verified, we proceeded to test the feasibility of tissue-deficit compensation using our single absorber modulator. As an example, we considered a mantle field technique. Materials and methods: To evaluate the accuracy of the method employed in calculating dose distributions delivered in 1D non-uniform fields, three different fluence profiles, which could be considered as a small sample representative of clinically relevant applications, were selected. The incident non-uniform fluences were simulated by the sum of simple blocked fields (i.e. with rectangular `strip' blocks, one per beam) properly weighed by the `modulation factors' F i , defined in each interval of the subdivided profile as the ratio between the desired fluence and the open field fluence. Depth dose distributions in a cubic phantom were then calculated by the TPS and compared with the corresponding doses (at 5 and 10 cm acrylic depths) delivered by the single absorber modulation system. In the present application, the absorber speed profile able to compensate for the tissue deficit along the cranio-caudal direction and then homogenizing the dose distribution on a `midline' isocentric plane with sufficient accuracy can be directly derived from anatomic data, such as the SSDs (source–skin distances) along the patient contour. The compensation can be verified through portal dosimetry techniques (using a traditional port film system). Results: The technique was tested in isocentric conditions on the humanoid RANDO phantom in a clinically suitable situation. The agreement between expected/calculated and measured incident/exit dose profiles was found to be within 4%, with deviations generally around 1–2%. As for the PB accuracy investigation for dose calculations in non-uniform fields, calculated versus measured dose profiles were found to be in good agreement, indicating a satisfactory accuracy of the method employed for dose calculation in 1D non-uniform photon beams. A better performance should be expected if the incident fluences could be directly inserted in the TPS. Conclusions: The results show that the proposed technique should be sufficiently reliable for clinical application. The main advantages are its simplicity and the possibility of application on Linacs which have no complex options for dynamic control of collimators.